Exploring the Relationship Between Education and Economic Growht: A Critical Review Literature - Daniel Pasaribu (Edumaspul: Jurnal Pendidikan, 2024)
Education and economic growth are closely interrelated. Education enhances individual skills and knowledge, which can increase productivity and promote economic growth. On the other hand, economic growth can increase access to education and other resources needed to improve the quality of education. This study aims to critically review the literature on the relationship between education and economic growth. This study used a literature review method to analyze relevant literature on this topic. The literature analyzed included empirical studies, economic theory, and policy papers. Research findings show that there is a strong positive relationship between education and economic growth. Individuals with higher levels of education generally have higher incomes and are more productive. Countries with higher levels of education also tend to have higher economic growth. The study's findings have important implications for education and economic policy. Increased investment in education can improve individual skills and knowledge, which can promote economic growth and improve people's well-being.